ALMOST PRIME LEFT FRACTION IDEAL AND FULLY WEAKLY PRIME LEFT RINGS - Nur Hidayat Taufiqurrahman, M
The work by Abouhalaka and Findik , titled ”Almost Prime Ideals in Noncommutative Rings,” introduces the concept of rings in which every right ideal is an almost prime ideal, which called fully almost prime right ring. This paper applies this concept to weakly prime left ideals and aims to demonstrate that the properties established for almost prime right ideals by Abouhalaka and Findik also hold for weakly prime left ideals under certain additional conditions. Additionally, the authors provide supplementary results for the fraction module, which constitutes an almost prime ideal.